AN EMPIRICAL ANALYSIS OF INTERNAL, EXTERNAL FACTORS AND COVID 19 ON STOCK RETURN OF COAL MINING COMPANIES IN INDONESIA - Anwar A.S., Khairul
This study explored the determinants of stocks return in coal firms in Indonesia. A quantitative analysis was performed based on the annual report of listed firms by employing a generalized least square with panel data to estimate the result. The quarterly data panel of 12 coal mining companies from Q1 2016 until Q2 2021 were used. Results showed that Indonesia Coal Sales Export and Net Profit Margin have positive impact on stocks price. By contrast, Indonesia Coal Production showed a negative impact together with Domestic Coal Sales. In addition, dummy variable for pandemic covid 19 revealed that pandemic had positive significant effect on stock return.